Antimicrobial Resistance of Faecal Escherichia coli Isolates from Pig Farms with Different Durations of In‐feed Antimicrobial Use. (10th September 2015) - Gibbons, J. F.; Boland, F.; Egan, J.; Fanning, S.; Markey, B. K.; Leonard, F. C.
Summary: Antimicrobial use and resistance in animal and food production are of concern to public health. The primary aims of this study were to determine the frequency of resistance to 12 antimicrobials in Escherichia coli isolates from 39 pig farms and to identify patterns of antimicrobial use on these farms. Further aims were to determine whether a categorization of farms based on the duration of in‐feed antimicrobial use (long‐term versus short‐term) could predict the occurrence of resistance on these farms and to identify the usage of specific antimicrobial drugs associated with the occurrence of resistance. Escherichia coli were isolated from all production stages on these farms; susceptibility testing was carried out against a panel of antimicrobials. Antimicrobial prescribing data were collected, and farms were categorized as long term or short term based on these. Resistance frequencies and antimicrobial use were tabulated. Logistic regression models of resistance to each antimicrobial were constructed with stage of production, duration of antimicrobial use and the use of 5 antimicrobial classes included as explanatory variables in each model. The greatest frequencies of resistance were observed to tetracycline, trimethoprim/sulphamethoxazole and streptomycin with the highest levels of resistance observed in isolates from first‐stage weaned pigs. Differences in the types of antimicrobial drugs used were noted between long‐term and short‐term use farms. Categorization of farms as long‐ or short‐term use was sufficient to predict the likely occurrence of resistance to 3 antimicrobial classes and could provide an aid in the control of resistance in the food chain. Stage of production was a significant predictor variable in all models of resistance constructed and did not solely reflect antimicrobial use at each stage. Cross‐selection and co‐selection for resistance was evident in the models constructed, and the use of trimethoprim/sulphonamide drugs in particular was associated with the occurrence of resistance to other antimicrobials.